The fear that stalks : gender-based violence in public spaces - Pilot, Sara.; Prabhu, Lora.; Centre for Equity and Inclusion (New Delhi, India) (New Delhi : Zubaan, 2012)
Papers presented at a two-day conference on Gender-based violence in public spaces : challenges and solutions, held at New Delhi in October 2010 moderated by CEQUIN.
"Published in collaboration with UNDP and CEQUIN"--P. facing t.p.
Includes bibliographical references.
Keywords: Women -- Violence against -- India -- Congresses; Women -- Legal status, laws, etc. -- India -- Congresses; Family violence -- India -- Congresses; Public spaces -- India -- Social conditions -- Congresses